The reception of Robert Alexy's work in Anglo-American jurisprudence1. (3rd April 2019) - Rivers, Julian
ABSTRACT: At first sight, the work of the German legal philosopher and constitutional theorist, Robert Alexy, appears to offer a welcome counter-example to the general insulation of Anglo-American jurisprudence from continental European influences. Over the last 30 years, his ideas and writings have become increasingly available in English, and they have stimulated a growing engagement in response. However, this immediate impression masks an unevenness in the reception of his work. In this article I trace the history and extent of this reception, contrasting its variability with the internally systemic and coherent quality of Alexy's entire oeuvre . I suggest that the causes for this variability are to be found in the intellectual climate of modern anglophone jurisprudence, in which work in the Kantian legal-philosophical tradition is unfamiliar or viewed with caution. A deeper theoretical development needs to take place if his work is to be appreciated holistically. However, there are signs that such a development is taking place, and it is possible that in time the reception of Alexy's work will be seen to be part of that longer-term process.